Page Design Attributes and Browsing Behaviour on the Web - Kopak, R.W. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
Few empirically based standards exist for Web document design. This study collected data on twelve participants who were asked to browse a selected set of Web sites. Participants were also asked to complete a number of tasks. The data were applied to four hypotheses and a research question that were concerned with the use of graphic elements, depth and breadth of hierarchy ...